Baśniowi bohaterowie w przestrzeni edukacji z perspektywy dziecięcych odbiorców - Kaliszewska-Henczel, Magdalena (Rocznik Pedagogiczny, 2020)
The paper explores the nature of fairy tales’ protagonists in a traditional literary fairy tale and in the modern one from the perspective of pupils who are from seven to ten years old. The fairy tales are often being used in the early childhood education field as the starting point for school plays, as play themes or as a ‘background’ for language, science or mathematics activity. Children’s symbolic perception of the fairy tales’ characters and their relationships reveals that there is a way of pupils’ reception of texts in which those texts are treated (and analysed) as a work of literary art. The article presents the results of research, in which – through the application of a non-verbal method – children indicated the interactions between Cinderella from the traditional literary fairy tale and a daisy from Hans Christian Andersen’s story (The Daisy).